KESIAPAN STANDAR NASIONAL INDONESIA DALAM RANGKA HARMONISASI STANDAR ASEAN - Firman Mutakin; Aziza R Salam (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
A mapping on priority products for harmonization is urgently needed in order to prepare Indonesia National Standard (Nasional Indonesia/SNI) for ASEAN standard harmonization. By using five parameters (export value, competitiveness, SNI status, test laboratory, and LSPro) for electronic products and electronic products and electric several findings can be described as follow:8 (eight) product standar have better readiness to be listed as top priority for harmonization , 6 (six) standards should be next in line for harmonization and 50 (fifty) standars become the las priority for harmonization are : copper cathodes; sound system equipment part-5 sound system; capacitor for electrical apparatus; floursecent lamp incandescent lamp incandescent starter; ceramic block for terminal; Zinc flat steel wire shielded electric cables; alternating current lamp fitting; and tube shape flourescent lamp for general use. To further encourage Indonesia readiness towards standard harmonization in ASEAN level, several crash programmes need to be initiated, such as: 1. Immediate revision for the top priority standards which fall into the first priority scale according to the latest international standard revision guidelines; 2. To facilitate the development quality test institution and LSPros which hold complete competence and distribute accordingly with their industry distributions.